ANALYSIS OF INTERNAL COMMUNICATION AND WORK SYSTEMS ON WORK PRODUCTIVITY WITH MOTIVATION AS AN INTERVENING VARIABLE IN THE OFFICE HEAD OF MEDAN BELAWAN DISTRICT - Dharmazie Dwi Ilham; Mesra B; Elfitra Desy Surya (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to analyze the influence of internal communication and work systems on work productivity with motivation as an intervening variable at the Medan Belawan District Office. This study uses a quantitative approach with a survey method by distributing 51 questionnaires to employees as respondents. The sample was determined using a purposive sampling technique so that the data obtained was in accordance with the research needs with a total of 51 respondents. Data analysis was carried out using path analysis techniques to measure the direct and indirect effects between variables. The results of the study indicate that internal communication has a positive and significant effect on work motivation as well as its effect on work productivity. Internal communication has a positive and significant effect on work motivation as well as its effect on work productivity. The work system has a positive and significant effect on work motivation but has a positive but not significant effect on work productivity. Work motivation also has a positive and significant effect on employee work productivity. In addition, internal communication and work systems have been shown to have a significant direct effect on work productivity. Thus, motivation acts as an intervening variable that mediates the effect of internal communication and work systems on work productivity. The findings of this study are expected to be input for management in increasing work productivity through improving internal communication, developing effective work systems, and increasing employee work motivation.